Women Candidates, Social Capital, and Family Networks in the 2024 Indonesian Local Election - Raegen Harahap (UIN Sunan Gunung Djati, 2025)
This article explores the factors driving the political success of non-elite female candidates in the 2024 Ogan Ilir Regency legislative elections. While recent research on women’s political representation in Indonesia often emphasizes elite-driven path, this study highlights the agency of female candidates who navigate alternative, non-elite pathways. Through grassroots mobilization, cultural alignment, and the strategic use of familial resources, these candidates build trust and engage diverse voter bases. Using the concepts of social capital, relational networks, and family-focused strategies, the study reveals that integrating these forms of capital enables candidates to adapt effectively to socio-political challenges. The findings demonstrate that non-elite female candidates can overcome structural barriers and achieve electoral success by leveraging personal relationships and community networks. This study provides valuable insights into advancing women’s representation in patriarchal societies and contributes to broader discussions on gender equity in Southeast Asia.